2017
DOI: 10.1292/jvms.16-0086
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the ribosomal DNA unit of <i>Sarcocystis singaporensis</i>, <i>Sarcocystis zamani</i> and <i>Sarcocystis zuoi</i> from rodents in Thailand

Abstract: Sarcocystis species are heteroxenous cyst-forming coccidian protozoan parasites with a wide host range, including rodents. In this study, Sarcocystis spp. samples were isolated from Bandicota indica, Rattus argentiventer, R. tiomanicus and R. norvegicus across five provinces of Thailand. Two major groups of Sarcocystis cysts were determined in this study: large and small cysts. By sequence comparisons and phylogenetic analyses based on the partial sequences of 28S ribosomal DNA, the large cysts showed the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…At these two loci, there was high similarity between S . zuoi detected in the Malayan field rat Rattus tiomanicus by Watthanakaiwan et al [ 12 ], and the parasite found in the Asian gray shrews in the present study. However, the thin-walled sarcocyst of S .…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…At these two loci, there was high similarity between S . zuoi detected in the Malayan field rat Rattus tiomanicus by Watthanakaiwan et al [ 12 ], and the parasite found in the Asian gray shrews in the present study. However, the thin-walled sarcocyst of S .…”
Section: Methodssupporting
confidence: 74%
“…However, the thin-walled sarcocyst of S . zuoi described by Watthanakaiwan et al [ 12 ] unambiguously differs from the thick-walled sarcocyst of S. zuoi proposed by Hu et al [ 13 ] in the Norway rat Rattus norvegicus . Therefore, the S .…”
Section: Methodsmentioning
confidence: 62%
“…Among the four available sequences of S . zuoi from Thailand (KU341118-21; Watthanakaiwan et al, 2017 ) we restricted our analysis to KU341120, because it ranked first in the BLAST search and represented the longest nt sequence from that location. Other taxa included S. tupaia (FJ827486; because published sequences FJ827485-88 are identical, only one was included here; Xiang et al, 2010 ), the only known 18S rDNA sequence from a treeshrew to date, members of the ‘ S .…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown recently that a complete ITS1-5.8S rDNA-ITS2 region could be useful for the evolutionary studies of Sarcocystis spp. from small mammals [47]. Other investigators demonstrated that mitochondrial cytochrome b (cytb) was a better choice than 18S rDNA and cox1 for the discrimination of the closely related S. cymruensis and S. ratti that parasitize rats [35].…”
Section: Sarcocystis Species Identification and Richness In Small Mam...mentioning
confidence: 99%